Language, the "Diabetes Restricted Code/Dialect, " and What It Means for People With Diabetes and Clinicians. (February 2017) - Dunning, Trisha; Speight, Jane; Bennett, Craig
Purpose: The purpose of the paper is to explore the notion of a diabetes language restricted code or "dialect" and its effect on people with diabetes. Language is a complex phenomenon comprising verbal and nonverbal components used to communicate in human interactions. Methods: Information was collected from a literature review, during clinical consultations, and from an email survey. Results: Language and the way clinicians use language affect motivation, behaviors, and outcomes of people with diabetes. Language is influenced by culture, experience, and familiarity with words and their use and is idiosyncratic. "Diabetes" is a particular restricted code or dialect that people with diabetes gradually learn to speak, usually after they are diagnosed with diabetes. The diabetes dialect contains many metric and target words and very few positive, encouraging words, and it is often discriminatory, negative, judgmental, labelling, distressing, and stigmatizing: for example, victim, sufferer, and lifestyle disease . Conclusion: Language codes/dialects can compound the already high levels of emotional distress and self-care burden associated with living with diabetes and can affect outcomes. The information presented in this article will be useful for clinicians caring for people with diabetes and will be helpful for professionals who develop information for people with diabetes and those who create policies and guidelines.